Improving medical students' confidence in end‐of‐life consultations. (30th July 2020) - Bansal, Aarti; Monk, Alice; Norman, Megan; Fingas, Samuel
Summary: Background: End‐of‐life discussions are associated with improved quality of care for patients. In the UK, the General Medical Council outlines a requirement for medical graduates to involve patients and their families in discussions on their care at the end‐of‐life. However medical students feel ill‐equipped to conduct these discussions. Methods: In 2018, Sheffield Medical School introduced a small group role‐play session on end‐of‐life discussions for all final year medical students. Scenarios were devised to improve confidence in the following learning domains: communicating prognosis with patients and family; ascertaining patient's goals, values and preferred place of death; discussing escalation of treatment, discussing do not attempt resuscitation orders, care in the dying phase of illness and pre‐emptive prescribing. Evaluation was conducted over 16 weeks with a before and after questionnaire. Students rated their confidence in the above learning domains on a Likert‐style scale and explained their ratings in free‐text boxes. Results: There was a 76% response rate to the questionnaire and analysis showed statistically significant improvements in confidence across all learning domains following the session. Qualitative analysis of free‐text responses showed that prior to the sessions, students expressed low confidence due to lack of experience and fear of upsetting patients. After the session students felt they had gained skills but expressed persistent anxiety and a desire for further practice. Conclusions: Our innovation suggests that the opportunity to experience End‐of‐life discussions through role‐play can significantly improve students' confidence in conducting these conversations. However, repeated sessions are likely necessary for students to feel prepared upon graduation.